Solvent-free selective oxidation of benzyl alcohol by molecular oxygen over uranium oxide supported nano-gold catalyst for the production of chlorine-free benzaldehyde - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Green Chemistry, 2007)
A detailed investigation on the production of chlorine-free benzaldehyde in the solvent-free oxidation of benzyl alcohol by O-2 over nano-gold supported on U3O8 has been carried out. Influence of different catalyst parameters (different methods of gold deposition on U3O8, gold loading and particle size, and catalyst calcination temperature) and reaction conditions (reaction period and temperature) on the process performance has been studied. The catalyst containing gold at higher concentration and with smaller gold particles showed the better process performance (higher benzyl alcohol conversion and benzaldehyde yield or selectivity). The benzyl alcohol conversion is largely increased but the selectivity for benzaldehyde is slightly decreased (while that of benzyl benzoate is increased) with increasing the reaction period or temperature. In the presence of solvent (viz. tolune, p-xylene, DMF or DMSO), the process performance was found to be inferior to that observed in the absence of any solvent. Substituted benzyl alcohols also can be oxidized by O-2 to corresponding aldehydes with high yield and/or selectivity, using the catalyst in the absence of any solvent.

Supported copper oxide as a highly active/selective catalyst for the epoxidation of styrene by TBHP to styrene oxide - Choudhary, Vasant R.; Jha, Rani; Chaudhari, Nitin K.; Jana, Prabhas (Catalysis Communications, 2007)
Liquid phase epoxidation of styrene by anhydrous and aqueous TBHP to styrene oxide has been studied under reflux, using different supported CuO (viz. Cuo/Si-MCM-41, CuO/Al2O3, CuO/Ga2O3 and CuO/In2O3) as easily separable and reusable heterogeneous catalysts. The CuO/Ga2O3 catalyst showed the best performance in the epoxidation by aqueous TBHP. The CuO supported on In2O3 or Si-MCM-41 also showed very good performance in the epoxidation but only by anhydrous TBHP. However, the CUO/SiO2 catalyst, however, showed very good performance in the epoxidation by both the anhydrous and aqueous TBHP. Influence of the reaction conditions (temperature, time and TBHP/styrene ratio) on the epoxidation by aqueous TBHP over the best catalyst (CuO/Ga2O3) has been investigated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: CuO/Al2O3; CuO/Ga2O3; CuO/In2O3; Cuo/Si-MCM-41; CuO/SiO2; epoxidation; styrene; Styrene oxide; tertiary butyl hydroperoxide

Synergetic effect of two halogen promoters present in acidic reaction medium or catalyst on the H2O2 formation (in H-2-to-H2O2 oxidation) and destruction over Pd/C (or Al2O3) catalyst - Choudhary, Vasant R.; Jana, Prabhas (Journal of Catalysis, 2007)
A strong synergetic effect of two different halide anions (F- and I-, Cl- and I-, Cl- and Br-, and F- and Br-) at optimum concentration in the catalyst or in an acidic reaction medium was observed in the H-2-to-H2O2 oxidation over Pd/C, Pd/Al2O3, and halogenated Pd/Al2O3 catalysts. The synergetic effect promote, the net H2O2 formation by inhibiting the H2O2 decomposition and hydrogenation reactions. The effect is most pronounced for the combination of fluoride (or chloride) and iodide anions. The Br (1 wt%)-F (1 wt%)-Pd (5 wt%)/Al2O3 catalyst showed very high H2O2 yield (59%)/selectivity (60%) in the H-2-to-H2O2 oxidation. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: H-2-to-H2O2 oxidation; H2O2 decomposition H2O2 hydrogenation; halogen promoter; Hydrogen peroxide; Pd/Al2O3; Pd/C; synergetic effect

Selective epoxidation of styrene to styrene oxide by TBHP using simple transition metal oxides (NiO, CoO or MoO3) as highly active environmentally-friendly catalyst - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Catalysis Communications, 2008)
Simple transition metal oxides, such as NiO, CoO or MoO3, etc. show high catalytic activity for the selective epoxidation of styrene to styrene oxide by TBHP. The order of choice for different transition metal oxides for epoxidation is NiO > CoO > MoO3 > Cr2O3 > Fe2O3 > ZnO >= U3O8 >> TiO2 >> MnO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CoO; epoxidation; MoO3; NiO; styrene; Styrene oxide; TBHP